Significant Correlation between Regional Tissue Oxygen Saturation and Vital Signs of Critically Ill Infants - Massa-Buck, Beri; Amendola, Virginia; McCloskey, Reagan; Rais-Bahrami, Khodayar (Frontiers in Pediatrics, 2017)
Background: Near-infrared spectroscopy (NIRS) has been used to noninvasively measure specific tissue oxygen saturation (StO2) continuously. Cerebral autoregulation status can be derived from NIRS and arterial blood pressure. The relationship of both cerebral and somatic StO2, fractional tissue oxygen extraction (FTOE), and cerebro-splanchnic oxygenation ratio (CSOR) to measured vital signs parameters for NICU patients has not been well studied. Objective: Determine if significant relationships between brain and somatic StO2, brain and somatic FTOE, and CSOR parameters to vital signs for neonates exist. Assess relationship between pressure passivity index, cerebral autoregulation and mean blood pressure (MBP). Design/Methods: Neonates weighing <5 kg, preferentially with an arterial catheter, were enrolled in the study. FORE-SIGHT Elite (CASMED Inc., Branford, CT, USA) cerebral and somatic NIRS sensors were placed over the abdominal right upper quadrant and right frontal-temporal area of the forehead for 24 hours. Vital signs including arterial MBP were recorded simultaneously from the patients’ bedside monitor. Data was averaged into 60 second windows and analyzed using linear regression. Results were stratified by gestational age (GA), birth weight (BW), and presence of brain abnormality. Results: Data was obtained from 27 subjects (GA 22.2 to 42 weeks). Two subjects did not have an arterial line, thus they were not included in the MBP measurements. There were ~28000 to 31000 paired data points per comparison. Significant positive and negative correlations (p value <0.0001) were noted between NIRS parameters and vital signs. When stratified by BW, there was a positive correlation between brain StO2 (StO2B) and MBP in the <1500g BW group (r=0.193) and a negative correlation in >1500g group (r=0.057). Brain and somatic FTOE in <1500g BW revealed a negative correlation to MBP (r=0.172 and r=0.086, respectively). In patients with an abnormal brain scan, a positive correlation was noted between StO2B and MBP (r=0.354) and a negative correlation was noted between FTOE-B vs. MBP (r=0.305). Generated pressure passive index plots suggested good cerebral autoregulation at low normal MBP ranges for lower weight and GA subjects. Conclusions: There is a significant correlation between cerebral and somatic StO2 and FTOE to measured vital sign parameters in NICU patients.